Child Education-Induced Migration and Its Impact on the Economic Behaviors of Migrated Households in China - Weibo Yan; Peng Nie (Institute of Labor Economics (IZA), 2021)
Using the 2011-2013 China Migrants Dynamic Survey, this paper utilizes the quarter of the year in which a child was born as an instrumental variable to measure child education shock and explores its impact on migrated households. We only find significant education-induced migration among boys, which we attribute to son preference in China. Due to child education-induced migration, the per capita household consumption increases by 56.7%, the savings rate decreases by 40.3%, and remittances sent home decline by about 1.3 monthly household incomes, however, there are no effects on income, food consumption, and house rent. After exploring the mechanisms underlying child education-induced migration, we find that children migrate with their parents for a better education in urban areas. Because of the closure and consolidation of rural primary schools, children are forced to migrate due to their education needs. The accessibility of primary schools in urban areas is also responsible for migration decisions regarding children. This paper facilitates understanding of how Hukou influences gender inequality in China. We also provide evidence to show that the segregation of the education system through Hukou is a possible explanation for the low consumption rate of migrants.
Keywords: O15; I28; D14; 330; education-induced migration; Hukou; son preference; economic behaviors